2016
DOI: 10.1111/all.12911
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of human IgE-expressing B cells and plasma cells

Abstract: BackgroundIgE-expressing (IgE+) plasma cells (PCs) provide a continuous source of allergen-specific IgE that is central to allergic responses. The extreme sparsity of IgE+ cells in vivo has confined their study almost entirely to mouse models.ObjectiveTo characterize the development pathway of human IgE+ PCs and to determine the ontogeny of human IgE+ PCs.MethodsTo generate human IgE+ cells, we cultured tonsil B cells with IL-4 and anti-CD40. Using FACS and RT-PCR, we examined the phenotype of generated IgE+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 45 publications
4
66
0
Order By: Relevance
“…A particularly striking case is that of the IgE BCR, which in mouse studies was shown to have an antigen-independent constitutive activity leading to increased PC differentiation, reduced GC B cell responses, and virtually undetectable Bmems (Haniuda et al, 2016;He et al, 2015;Yang et al, 2014. Recent evidence from cultured human B cells (Ramadani et al, 2017) and singlecell RNA-seq of blood samples from allergic patients (Croote et al, 2018) provides further evidence for a bias of IgE B cells to differentiate into PCs. Another factor that can influence the propensity to become a PC versus a GC cell is the chronic exposure to low avidity autoantigen.…”
Section: Plasma Cell Responsesmentioning
confidence: 99%
“…A particularly striking case is that of the IgE BCR, which in mouse studies was shown to have an antigen-independent constitutive activity leading to increased PC differentiation, reduced GC B cell responses, and virtually undetectable Bmems (Haniuda et al, 2016;He et al, 2015;Yang et al, 2014. Recent evidence from cultured human B cells (Ramadani et al, 2017) and singlecell RNA-seq of blood samples from allergic patients (Croote et al, 2018) provides further evidence for a bias of IgE B cells to differentiate into PCs. Another factor that can influence the propensity to become a PC versus a GC cell is the chronic exposure to low avidity autoantigen.…”
Section: Plasma Cell Responsesmentioning
confidence: 99%
“…Whether the two isoforms of primate mIgE are differentially used by certain B cell populations is insufficiently investigated. Experiments using in vitro cultures of human tonsillar B cells indicated that the EMPD‐containing long mIgE isoform may be predominantly expressed in freshly switched germinal center‐like B cells, whereas the EMPD‐deficient short isoform seems to be predominantly used in more differentiated plasmablast‐like cells …”
Section: Complexity Of Mige‐bcr Expression In Human B Cellsmentioning
confidence: 99%
“…To validate that our enhanced staining technique was capable of detecting IgE + MBCs, we stimulated PBMCs in culture with IL-4 + anti-CD40, which is known to induce IgE class-switching (34). As expected, culturing under these conditions resulted in the robust emergence of IgEsecreting cells and IgE as detected by total IgE ELISPOT and ELISA, respectively (Fig.…”
Section: Development Of Enhanced Flow Cytometric Methods For Detectionmentioning
confidence: 55%